Pyramiding of submergence tolerance and brown planthopper resistance genes into Putra-2 rice variety through marker-assisted backcrossing - Haliru, Bello Sani (2022)
Rice is a main food crop for majority of the world’s population. It is cultivated in over 100 countries on about 164 million hectares, mostly in the tropical and subtropical regions, and predominantly in Asia. Submergence stress and brown planthopper (BPH) infestation are the two main production constraints of rice in Asia. Gene pyramiding is a strategy whereby two or more genes are combined into a single variety to confer resistance to two or more biotic/abiotic production constraints of rice. The markerassisted backcrossing (MABC) was used to incorporate BPH resistant genes from Rathu Heenati rice variety (Donor parent) into the genome of Putra-2 (Recurrent parent, high yielding and submergence tolerant (SUBT), but BPH susceptible). The main objective of this research was to develop high yielding, SUBT and BPH resistant rice variety for commercial cultivation in Malaysia. The specific objectives were; to identify polymorphic simple sequence repeat (SSR) markers linked to submergence tolerance and BPH resistance genes/QTLs, to identify polymorphic SSR markers for recurrent parent genome recovery, to introgress BPH resistance genes/QTLs from Rathu Heenati to Putra- 2 rice variety, to quantify the percentage genome recovery of Putra-2 carrying BPH resistance genes/QTLs in BC1F1, BC2F1 and BC2F2 populations, and to validate the presence of submergence tolerance and BPH resistance genes/QTLs in backcross progenies with polymorphic linked markers and phenotypic selection. Out of 316 SSR markers screened, 79 (25%) markers exhibited polymorphism between the two parents. These markers were applied to determine the recovery of recurrent parent genome (RPG) in the BC1F1, BC2F1 and BC2F2 generations. The mean RPG recovery of the four chosen BC1F1 progenies was 80.3%. These progenies acquired the genes/QTLs of the foreground markers (RM8300, RM545 and RM544) and were used to develop the BC2F1 population. Due to two repeated generations of backcrossing and one cycle of selfing, the RPG recovery increased from 80.3% in the BC1F1 to 97.2% in BC2F2 selected lines. The marker genotypic segregation analyses using Chi-square test in the BC1F1 (1:1), BC2F1 (1:1) and BC2F2 (1:2:1) populations for the observed and expected proportions, showed non-significance probability at 5% level for both SUBT and BPH resistant loci, thus conforming to Mendelian single dominant gene inheritance model. Similarly, the phenotypic segregation for the observed and expected ratios (3:1) in BC2F2 population for submergence tolerance and BPH resistance loci, using Chi-square analysis, indicated non-significance probability at 5% level, and thus obeying Mendelian single gene inheritance model. On the other hand, phenotypic segregation for observed and expected fractions for two gene inheritance model (9:3:3:1) and epistatic effect (15:1) for SUBT and BPH resistance, had revealed significant difference (P<0.05) between the ratios using Chi-square analysis. Hence, indicating absent of two gene inheritance model and epistatic effect, in the present population. Validation experiments for SUBT and BPH resistance in improved pyramided lines indicated that all the selected improved lines had significantly (P<0.05) differed with negative checks, but however, statistically similar with positive checks. Mean comparison of yield and agro-morphological traits between Putra-2 variety and the selected improved lines showed no significant difference using independent t-test at 5% level of probability, and thus revealing that all the traits were recovered. In conclusion, ten improved pyramided rice lines were developed, namely: BC1-P1-P15-P6, BC1-P1-P15-P13, BC1-P1-P15-P16, BC1-P3-P13-P9, BC1-P3-P13-P19, BC1-P7- P9-P1, BC1-P7-P9-P11, BC1-P7-P9-P17, BC1-P19-P1-P3 and BC1-P19-P6-P10. The ten improved lines are recommended for further large scale evaluation and multi-location trials at rice granary areas to identify superior lines with high yield, submergence tolerance and brown planthopper resistance for commercial cultivation in Malaysia.